Sodium fluxes and silicon at the root plasma membrane: a paradigm shift?. (24th March 2018) - Santa-María, Guillermo E; Rubio, Francisco
Abstract : This article comments on: Flam-Shepherd R, Huynh WQ, Coskun D, Hamam AM, Britto DT, Kronzucker HJ. 2018. Membrane fluxes, bypass flows, and sodium stress in rice: the influence of silicon. Journal of Experimental Botany 69, 1679–1692 .